Effects and Quality of Stroke Rehabilitation of BAR Phase D - Bussmann, Marie-Luise; Neunzig, Hans-Peter; Gerber, Joachim; Steinmetz, Jochen; Jung, Svenja; Deck, Ruth (Neurology International Open, 2018)
Background Stroke is a major public health problem of enormous epidemiological significance. Each year, approximately 200.000 people in Germany suffer a stroke. Stroke is the third leading cause of death and the most common cause of acquired disabilities in adults. About one fourth of stroke survivors report severe limitations in activities of daily living three months after acute stroke. The most common post-stroke conditions are motor and cognitive dysfunctions as well as affective problems. Stroke rehabilitation plays a crucial role in coping with stroke sequelae. The large number of strokes and the often debilitating consequences raise the question to what extent participation can be increased by medical rehabilitation.Methods A prospective, multicenter survey study was conducted in six neurological inpatient rehabilitation centers. Recruitment focused on patients with recent acute stroke and disease severity corresponding to BAR phase D. Patients completed questionnaires at three points of measurement: at the beginning and at the end of the inpatient rehabilitation and after four months. Primary outcome was participation, secondary outcomes included several parameters of subjective well-being. Furthermore, utilization of aftercare and satisfaction with the rehabilitation program were measured.Results At the beginning of the rehabilitation, patients experienced severe limitations in participation and reduced subjective well-being. At the end of inpatient rehabilitation, significant improvements of small effect sizes for subjective well-being and medium effect sizes for participation were achieved. After four months, effects had decreased, yet improvements compared to baseline were still noticeable. Patient ratings of the rehabilitation program and the outcomes achieved were consistently positive. Two thirds of the patients were advised to make use of aftercare offerings and most patients (83%) participated in an aftercare program of any kind.Conclusions The results of this study support the notion that stroke rehabilitation has significant and sustainable effects. Participation in particular seems to improve through medical rehabilitation. Partly decreased effects after four months raise the question of adequate aftercare.
Keywords: stroke rehabilitation; participation; outcome quality; satisfaction